COVID 19 CHALLENGES IN DENTAL HEALTH CARE AND DENTAL SCHOOLS - Forna Norina (Romanian Society of Oral Rehabilitation, 2020)
The spread of Covid-19 in Europe represented a challenge both for dental health care providers and dental schools. The dental regulatory authorities provided guidance with instructions and recommendation for outbreak pandemic period that addressed to the limitation of contact with patients to only dental care emergencies and urgencies and to the implementation of strict safety measures to ensure the prevention of cross-infection with new coronavirus. Also, the opening of the most dental offices and clinics, after the closing of the emergency state, was accompanied by rules and recommendations aiming to ensure both safety and effectiveness of the dental activity in the post Covid 19 era. The dental schools faced new challenges related to disruption of dental students from clinical earning experiences, cancellation of scientific conferences, changes of plans and activities, blocking of academic contests for promotion and hiring of new academics and scientists, social isolation and psychological impacts on staff and students. During pandemic period most of the dental schools shifted to online teaching sharing high quality courses, clinical cases and problem-based learning tutorials by technological platforms, and redesigned theoretical and practical examens to allow the end of academic year. In the new context, the dental schools face challenges related to the need for redesigning of the clinical space and mixing the clinical and online dental education, the insurance of the safety of the dental students, teaching staff, and patients, the adjusting of the academic calendars, the maintenance of the academic and research activities as well as the continuity of the oral health care activities.